ANALISIS MISKONSEPSI MATEMATIKA MATERI PEMBULATAN DAN PENAKSIRAN BILANGAN PADA SISWA KELAS V SEKOLAH DASAR - Ilah Fadillah; Hepsi Nindiasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Misconceptions often occur in students, especially in mathematics learning. Rounding and estimating number material is a basic concept in numeracy learning. This study is a qualitative descriptive study that aims to describe the types of misconceptions and causes of misconceptions of fifth grade students in rounding and estimating number material. Misconceptions are classified into 2 types, namely conceptual errors and arithmetic operation errors. The subjects of the study were 13 fifth grade students of SDN Cigandeng 1. The instruments in this study were tests, interviews and documentation. The data analysis technique used was the Miles and Huberman data model analysis consisting of data reduction, data presentation and conclusions. The results of the study showed that the results of observations and interviews conducted by the researcher said that the mistakes made by students in solving problems related to rounding and estimating material included conceptual errors and operational errors in applying rounding and estimating material. These errors occur because students do not really understand how to round a number and estimate a correct word.